Biologically active area in low-rise high-denisty housing development with an example of Bialystok - Matys, Wojciech (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2019)
The biologically active area is one of the most important elements of residential development. Its size is determined by the percentage factor established in local spatial development plans and laws regulations. The publication was set minimum values ​​for this ratio for single-family and multi-family housing, and the outcomes were compared with a new type of housing, currently popular in Poland, low-rise high-density residential development. The studies were done on the example of the city of Bialystok, where there are many buildings of this new type of housing.